Doprowadź do najprostrzej postaci i oblicz wartośc liczbową wyrażeń.
a)4m-8n-1(-3m+4n)= dla m=1/7(jedna siódma),n=¾
b)1(9-4x)-1(3a-2)+1(3a+2)= dla a=½,x=2
c)1(3a-4b)-1(2a-4b)+1(3a-5b) = dla a=-½,b=1/5(jedna piąta)
d)3(2x+3y)-5(3x-y)-1(x-y)= dla x=-1,y=½
e)5a-2(3a-7)-3(a-3)-2a= dla a=¾
f)----------------------------- ----------
g)-2(a+b+c)-3(a-b+c)+4(a-b-c) = dla a=-1,b=-2,c=-3
h)3(x²-2x+5)-4(-x²+5x-7)-2x²= dla x=1
i)1-a(b-1)+2[-b(a+1)-0,5a]+2b= dla a=4/15(cztery pietnastę) b=¼
j)3[4x-(5y+3x)]-4[3x-(2x+3y)]= dla x=3,5 y=-5/6(pięc szóstych)











3

Odpowiedzi

Najlepsza Odpowiedź!
2010-04-05T22:51:08+02:00
A)4m-8n-1(-3m+4n)=4m-8n+3m-4n=7m+12n=7*1/7+12*¾=1+ 36/4=1+9=10

b)1(9-4x)-1(3a-2)+1(3a+2)=9-4x-3a+2+3a+2=13-4x+a=13-4*2+1*½=13-8+½=5½

c)1(3a-4b)-1(2a-4b)+1(3a-5b)=3a-4b-2a+4b+3a-5b=4a-5b=4*(-1/2)-5*1/5=-2-1=3

d)3(2x+3y)-5(3x-y)-1(x-y)=6x+9y-15x+5y-x+y=10x+15y=10*(-1)+15*1/2=-10+7 1/2=-2 1/2

e)5a-2(3a-7)-3(a-3)-2a=5a-6a+14-9a+9=-10a+23=-10*3/4+23=7 1/2+23=30 1/2

g)-2(a+b+c)-3(a-b+c)+4(a-b-c)=-a-b-c -3a+3b-3c+4a-4b-4c=2a+6b+c=2*(-1)+6*(-2)+1*(-3)=-2-12-3=-17

h)3(x²-2x+5)-4(-x²+5x-7)-2x²=3x²-6x+15+4x²+20x+28=7x²+14x+43= 7*1²+14*1+43=7+14+43=64

i)1-a(b-1)+2[-b(a+1)-0,5a]+2b=1-ab+1a+2(-ab-1b-1/2a)+2b=1-ab+1a-2ab-2b-a+2b=1+3ab+2a+b=1+(3*4/15+3*1/4)+(2*4/15)+1/4=1+4/5+3/4+8/15+1/4= 1+4/4+4/5+8/15=2+12/15+8/15=2+20/15=2+4/3=3 1/3

j)3[4x-(5y+3x)]-4[3x-(2x+3y)]= 3[4x-5y-3x]-4[3x-2x-3y]=12x-15y-9x-12x+8x+12y=x-3y=3 1/2+12*(-5/6)=3 1/2 -10=-7,5
2010-04-05T22:52:35+02:00
A)
4m-8n-1(-3m+4n)=
4m-8n+3m-4n=
7m-12n=
7*1/7-12*3/4=
1-9=
-8

b)
1(9-4x)-1(3a-2)+1(3a+2)=
9-4x-3a+2+3a+2=
13-4x=
13-4*2=
13-8=
5

c)
1(3a-4b)-1(2a-4b)+1(3a-5b) =
3a-4b-2a+4b+3a-5b=
4a-5b=
4*(-1/2)-5*1/5=
-2-1=
-3

d)
3(2x+3y)-5(3x-y)-1(x-y)=
6x+9y-15x+5y-x+y=
-10x+15y=
-10*(-1)+15*1/2=
10+7,5=
17,5

e)
5a-2(3a-7)-3(a-3)-2a=
5a-6a+14-3a+9-2a=
-6a+23=
-6*3/4+23=
-4,5+23=
18,5

f)----------------------------- ----------
g)
-2(a+b+c)-3(a-b+c)+4(a-b-c) =
-2a-2b-2c-3a+3b-3c+4a-4b-4c=
-a-3b-9c=
-(-1)-3*(-2)-9*(-3)=
1+6+27=
34

h)
3(x²-2x+5)-4(-x²+5x-7)-2x²=
3x²-6x+15+4x²-20x+28-2x²=
5x²-26x+43=
5*1²-26*1+43=
5-26+43=
22

i)
1-a(b-1)+2[-b(a+1)-0,5a]+2b=
1-ab+a+2[-ab-b-0,5a]+2b=
1-ab+a-2ab-2b-a+2b=
1-3ab=
1-3*4/15*1/4=
1-5=
-4

j)
3[4x-(5y+3x)]-4[3x-(2x+3y)]=
3[4x-5y-3x]-4[3x-2x-3y]=
12x-15y-9x-12x+8x+12y=
-x-3y=
-3,5-3*(-5/6)=
-3,5+2,5=
-1

2010-04-05T23:02:11+02:00
A.)
4m-8n-1(-3m+4n)=
-12m+24mn+3m+16mn-32n²-4n=
-9*1/7+40*1/7*¾-32(¾)²-4*¾=
-9/7+40/7*¾-32*9/16-3=
-9/7+30/7-18-3=
-21/7-18-3=-23

b.)
1(9-4x)-1(3a-2)+1(3a+2)=
9-4x-3a+2+3a+2=
9-4x+2+2=
9-4*2+2+2=5

c.)
1(3a-4b)-1(2a-4b)+1(3a-5b)=
3a-4b-2a+4b+3a-5b=
4a-5b=
4*(-½)-5*⅕=
-2-1=-3

d.)
3(2x+3y)-5(3x-y)-1(x-y)=
6x+9y-15x+5y-x+y=
-10x+15y=
-10*(-1)+15*½=
10+7,5=17,5

e.)
5a-2(3a-7)-3(a-3)-2a=
5a-6a+14-3a+9-2a=
-6a+23=
-6*¾+23=
-9/2+23=18,5

g.)
-2(a+b+c)-3(a-b+c)+4(a-b-c)=
-2a-2b-2c-3a+3b-3c+4a-4b-4c=
-a-3b-9c=
-(-1)-3*(-2)-9*(-3)=
1+6+27=34

h.)
3(x²-2x+5)-4(-x²+5x-7)-2x²=
3x²-6x+15+4x²-20x+28-2x²=
5x²-26x+43=
5*(1)²-26*1+43=12

i.)
1-a(b-1)+2[-b(a+1)-0,5a]+2b=
1-a(b-1)+2(ab+b-0,5a)+2b=
1-ab+a+2ab+2b-a+2b=
ab+4b+1=
4/15*¼+4*¼+1=
1/15+1+1=2 i (jedna pietnasta)

j.)
3[4x-(5y+3x)]-4[3x-(2x+3y)]=
3(4x+5y-3x)-4(3x+2x-3y)=
12x+15y-9x-12x-8x+12y=
-17x+27y=
-17*3,5+27*-⅚=
-59,5-22,5=-82